Job performance of human resource management graduates from the employers’ and graduates’ perspectives - Sadang-Pascua, Dahlee; Montenegro-Villanueva, Jennifer (International Journal of Evaluation and Research in Education (IJERE), 2025)
Graduates’ job performance reflects their academic orientation in pursuit of their degrees. Thus, academic institutions should prepare students to be competitive, match the needs of the industry, and become worthy of employment after graduation. This research determines the job performance of human resource management (HRM) graduates in terms of their job competencies, career skills, and team performance from the perception of the graduates and their employers. A quantitative research method with statistical tools such as frequency, percentage, weighted mean, and Mann-Whitney U Test was used. Findings revealed a significant difference in the respondents’ perception, specifically in conveying ideas, use of IT, values, quality work, communication skills, human relations, technical, research, leadership skills, and team performance. The result also shows that graduates perceived themselves as excellent performers, which is in contrast to their employers’ perceptions of them as good performers only regarding their job competencies, career skills, and team performance. The differences in perceptions of the performance of the graduates depicts a mismatch between the academe and the industry requirements that result in a recommendation of thorough review and revision of the HRM curriculum, the teaching methodology, and the strategy of the academic institutions to meet the needs of the industry.